Love, Sex, Respect, and Physical Attractiveness in Marital Satisfaction and Remarriage: A Comparison Between Monogamous and Polygynous Marriages - Waqar Husain; Ammara Faheem; Aden Zaheer (Interpersona: An International Journal on Personal Relationships)
Studies on polygyny have been limited to socio-economic factors. The psychosocial aspects involved in the trend of having more than one wife were not studied earlier. The current study explored the role of love, sex, respect, and physical attractiveness in the marital satisfaction of polygynous husbands, monogamous husbands, and monogamous wives. A total of 611 participants from diverse cities in Pakistan took part in the study, comprising 57 polygynous husbands, 57 first wives of polygynous husbands, 57 second wives of polygynous husbands, 220 monogamous husbands, and 220 monogamous wives. Sukoon Marital Life Analysis scale was used to gather data. The results indicated a significant elevation in marital satisfaction among polygynous husbands with their second wives compared to the satisfaction levels of monogamous husbands. Additionally, second wives demonstrated significantly higher satisfaction with their husbands when compared to their first wives. These findings lead to the conclusion that second marriages exhibit notably higher levels of marital satisfaction for both polygynous husbands and their second wives in contrast to the satisfaction reported by monogamous husbands and wives. This study contributes valuable insights into the psychosocial dynamics of polygynous relationships.